Access to Communication Channels and Use of Family Planning among Women in Tanzania: Spatial and Socio-demographic Analysis - Kilugwe, Zuena; Ruheza, Sosthenes (Journal of Social and Development Sciences, 2018)
This study examined the relations and access to communication channels on the use of Family Planning (FP). Relationships between independent variables including access to communication channels and the use of FP services, and demographic characteristics were examined. This study used cross-sectional data from the Tanzania Demographic Health Survey and Malaria Indicator Survey (TDHS-MIS) of 2015-2016 from 11,127 women aged between 15-49 years. The sample was weighted to ensure representativeness. Univariate, bivariate and binary logistic regression analyses were used. Results in this study revealed a statically significant correlation between access to FP messages and use of family planning services (p<.001). Access to radio, television, printed media, and mobile phones was observed more among women who were never in a union, those with tertiary education, women in urban areas and among those within a high wealth index. Use of FP services increased with the fluency of access to FP messages. Printed media predicted more likelihood in the use of FP at 0.460, p<0.001; radio at 0.368, p<0.001; health facilities at 0.284, p<0.001 and education level at 0.276, p<0.001. The study concludes that despite the fact that there was a correlation between access to FP messages and the use of FP, the use or not use of the same is also influenced by factors.